Black Lives Matter: COVID, Crisis, and Color. Issue 1 (January 2021) - Rohan, Annie J.; Simpson, Kathleen Rice
Abstract : The COVID-19 pandemic has been stressful for nurses and childbearing women. Some women have experienced this stress more than others because they are disadvantaged, underserved, and have limited resources. Black women are especially at risk for poor pregnancy outcomes, not due to their race, but rather the long-standing structural racism and discrimination that are embedded in our health care system and society. MCN joins with other nursing organizations in recognizing racism as a public health crisis, one that nurses can do much to mitigate by their hands-on care, institutional and organizational leadership, policy making, and advocacy.